Intensi Memilih Pada Pemilih Pemula Ditinjau dari Konformitas Teman Sebaya (Resolusi: Jurnal Sosial Politik, 2025)
First-time voters represent a potential strategy for political parties' victory because, quantitatively, the number of first-time voters increases relatively from election to election. First-time voters, who lack voting experience, are easily influenced by their surroundings, including family, peers, and political parties themselves. This study aims to determine the relationship between voting intensity among first-time voters and peer conformity. The research method used was quantitative. Data were collected by distributing a questionnaire on a scale, with 44 first-time voters (n=44) responding. The results showed a positive relationship between peer conformity and first-time voter voting intensity, with an effective contribution of 6.60%. This indicates that peer conformity significantly influences first-time voter voting intensity. Conformity with peers is a significant factor in shaping first-time voter voting intensity. The higher the peer conformity, the higher the voting intensity among first-time voters.